Serum substitute in epithelial cell culture media: nonfat dry milk filtrate. - Fassolitis, A C (1981)
A number of milk types and milk fractions were investigated as possible substitutes for serum in cell culture media. A filtrate of reconstituted nonfat dry milk showed promise. Culture fluids containing 5% of the nonfat dry milk filtrate were used to propagate primary and continuous cell cultures, and the cell growth from these cultures was compared with that of cells grown in a serum-containing medium. The nonfat dry milk filtrate-supplemented medium supported the growth of all epithelial cells tested, but two fibroblast-type cultures failed to replicate. Cells grown in the medium containing the milk filtrate grew slowly for 2 to 3 days and then propagated to confluency in 6 to 8 days. Viable cell counts of 9 days were comparable to those of serum-grown cells that had been propagated for 7 days. Cells grown in the milk filtrate could be split 1 to 4 when subcultures were prepared. Cell growth could be stimulated by refeeding on days 2 to 3 or by the addition of 30 microM 2-mercaptoethanol to the growth medium. Virus susceptibility and titer comparisons with poliovirus 1, coxsackievirus B2, echovirus 7, and herpes simplex virus indicated that approximately the same data were obtained when either the nonfat dry milk filtrate-treated or the serum-treated cells were studied. The nonfat dry milk filtrate is inexpensive, is easily prepared, and is a substitute for serum in epithelial cell culture media.